2020
DOI: 10.1029/2019jb018644
|View full text |Cite
|
Sign up to set email alerts
|

Global‐Scale Full‐Waveform Ambient Noise Inversion

Abstract: We present the first application of full-waveform ambient noise inversion to observed correlation functions that jointly constrains 3-D Earth structure and heterogeneous noise sources. For this, we model and interpret ambient noise correlations as recordings of correlation wavefields, which completely eliminates the limiting assumptions of Green's function retrieval, such as equipartitioning and homogeneous random noise sources. Our method accounts for seismic wave propagation physics in 3-D heterogeneous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 94 publications
1
28
0
Order By: Relevance
“…Cross-correlations of ambient seismic noise form the basis of many applications in seismology from site effects studies (e.g., Aki, 1957;Roten et al, 2006;Bard et al, 2010;Denolle et al, 2013;Bowden et al, 2015) to ambient noise tomography (e.g., Shapiro et al, 2005;Yang et al, 2007;Nishida et al, 2009;Haned et al, 2016;de Ridder et al, 2014;Fang et al, 2015;Singer et al, 2017) and coda wave interferometry (e.g., Sens-Schönfelder and Wegler, 2006;Brenguier et al, 2008;Obermann et al, 2013;Sánchez-Pastor et al, 2019). Auto-correlations of the ambient noise are also increasingly used to study seismic interfaces as suggested by Claerbout (1968) (e.g., Taylor et al, 2016;Saygin et al, 2017;Romero and Schimmel, 2018) and to monitor subsurface properties (Viens et al, 2018;Clements and Denolle, 2018).…”
Section: Motivationmentioning
confidence: 99%
“…Cross-correlations of ambient seismic noise form the basis of many applications in seismology from site effects studies (e.g., Aki, 1957;Roten et al, 2006;Bard et al, 2010;Denolle et al, 2013;Bowden et al, 2015) to ambient noise tomography (e.g., Shapiro et al, 2005;Yang et al, 2007;Nishida et al, 2009;Haned et al, 2016;de Ridder et al, 2014;Fang et al, 2015;Singer et al, 2017) and coda wave interferometry (e.g., Sens-Schönfelder and Wegler, 2006;Brenguier et al, 2008;Obermann et al, 2013;Sánchez-Pastor et al, 2019). Auto-correlations of the ambient noise are also increasingly used to study seismic interfaces as suggested by Claerbout (1968) (e.g., Taylor et al, 2016;Saygin et al, 2017;Romero and Schimmel, 2018) and to monitor subsurface properties (Viens et al, 2018;Clements and Denolle, 2018).…”
Section: Motivationmentioning
confidence: 99%
“…An alternative to the direct discretisation of Eq. (6) combined with a Green's function database is on-the-fly computation of the correlation wavefield source G jm (x 2 , ξ)S nm (ξ) on the grid of a numerical wave propagation solver, and its use in a subsequent forward simulation (Tromp et al 2010;Fichtner 2014;Sager et al 2020). This approach trades the larger storage requirements of the Green's function database for larger computational requirements in an iterative inversion, where correlations must be computed for a sequence of noise source updates.…”
Section: Benchmarksmentioning
confidence: 99%
“…Even though it has been shown that the measurement is quite robust to unknown 3-D Earth structures (Sager et al 2018a), this could still lead to artifacts in the inversion. Sager et al (2020) invert for both, the structure and noise distribution simultaneously. This does, however, greatly increase the computational resources necessary to perform an inversion; particularly when considering high-frequency noise like the secondary microseisms.…”
Section: Real-data Inversionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sager et al (2018) investigated the full waveform ambient noise inversion that aims to extract the Green's function. Sager et al (2020) presented the first application about full-waveform ambient noise inversion to image subsurface. Tkalčić et al (2020) utilizes coda wavefield to investigate the earth's deep structure in earthquake seismology.…”
Section: Introductionmentioning
confidence: 99%